Comment on "Language and Emotion": Metaphor, Morality and Contested Concepts. (July 2016) - Roberson, Debi; Whitaker, Lydia
The nature of emotion concepts and whether there are any that are universally "basic" remains controversial, as acknowledged in the article "Language and Emotion." The suggestion that some emotions are embodied through a process of association between neural networks for bodily sensations (e.g., raised temperature) and neural circuitry dedicated to linguistic metaphor is interesting, but speculative. However, it is a hypothesis that risks relegating speakers of languages that lack sophisticated metaphors to a lower level on some scale of linguistic evolution.